The Level of Self-Regulated Learning and Self-Awareness in Science Learning in the Covid-19 Pandemic Era - Atmojo, S. E.; Muhtarom, T.; Lukitoaji, B. D. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2020)
The study aims to measure/determine the level of self-regulated and self-awareness in the science learning process, analyze students' self-regulated and self-awareness in science learning in the era of the Covid-19 pandemic. The design of this study was a modified experimental pre-test post-test control group design. This research was conducted from March to July 2020, with 200 research subjects divided into four classes. The research instrument consisted of questionnaires and test questions in the online form. The data obtained were analyzed using an analysis of scores and averages of the questionnaire filled out online. The subjects of this study were students who took science classes with a total of 200 students in the Elementary School Teacher Education, Faculty of Education, Universitas PGRI Yogyakarta. The results showed that the learning process of science could take place online using the Zoom application, Google Classroom, UPY e-learning, and WhatsApp group. Based on the analysis results, it is known that the average score of Self-Regulated Learning is 74.59 (good), the average score for Self-Awareness is 75.75 (good), and the average learning achievement is 74.59 (good). It can be concluded that this online science learning takes place to the maximum, has a value of usefulness that is seen from the average of independent learning numbers, self-awareness number, and student achievement, which are in good categories.